Seeking silk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Sericulture and silk production: a handbook by Prabhar Shekar and Martin Hardingham 1995 55pp price UKL6.95 ISBN 11 85339 317 7 IT Publications, 103/105 Southampton Row, London WC1B 4HH, UK